A research note: Are auditors unable to detect classification shifting or merely not willing to report it? Evidence from India. Issue 2 (August 2016) - Desai, Naman; Nagar, Neerav
Abstract: Research indicates that auditors fail to curb classification shifting in countries with relatively weaker legal institutions. However, it is not known whether auditors are unable to detect misclassifications or if they are merely not motivated to report them. We conduct two experiments to examine this issue. Our results indicate that auditors are sensitive to classification shifting while assessing fraud risk and audit effort. However, their willingness to report such misclassifications is affected by the overall legal liability regime of the region in which their clients operate. More specifically, our results indicate that the presence of weaker legal regimes reduce the litigation risk faced by auditors which make them less likely to report misclassifications. On the other hand, auditors are significantly more likely to report misclassifications by qualifying their audit report if a company is cross-listed in a country with strong institutional controls and legal regime.